PENEGAKAN HUKUM OLEH PENYIDIK PEGAWAI NEGERI SIPIL BEA DAN CUKAI TERHADAP TINDAK PIDANA PENYELUDUPAN MINUMAN KERAS ILLEGAL DI KABUPATEN SAMBAS - NIM. A1011191299, FASKALIS RENDY DAMELA (Jurnal Fatwa Hukum, 2023)
Abstract The phenomenon of the circulation of illegal goods entering through the West Kalimantan - Sarawak (Malaysia) border is a crucial problem from a legal perspective. Illegal goods entering the Aruk Border area, Sambas Regency, include: used clothes, used electronics, cigarettes made from foreign countries that do not have Indonesian excise stamps attached, liquor and other products. These goods entered Indonesian territory through the Aruk Border, Sambas Regency illegally with the aim of avoiding the obligation to pay import duties and distribution permits from the relevant technical agencies. The formulation of the problem in this research is why law enforcement by customs and excise civil servant investigators regarding the criminal act of smuggling illegal liquor in Sambas Regency is not yet optimal. The results of the research found a criminal act of smuggling liquor from Sarawak to the Aruk border, Sambas district, from various well-known brands. The number of criminal cases of smuggling of liquor from Sarawak to the Aruk border area of Sambas Regency during 2018-2022 was 53 cases, where in 2018 there were 10 criminal cases of smuggling, in 2019 there were 8 cases, in 2020 there were 5 cases, in In 2021 there were 14 criminal cases of smuggling, and in 2022 there were 26 criminal cases of smuggling of liquor from Sarawak to the Aruk border area, Sambas district and there were 20 criminal cases that were escalated to the prosecutor's level. Efforts to overcome smuggling by PPNS Customs and Excise by providing legal education to residents in the Aruk border area of Sambas district regarding Law Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 concerning customs; and tightening security in border areas, especially unofficial roads which are used as access for illegal liquor smuggling. Keywords: Smuggling, Law Enforcement, Smuggling Actors, Illegal Liquor, Law Enforcement Officials. Abstrak Fenomena beredarnya barang-barang illegal yang masuk melalui perbatasan Kalimantan Barat – Sarawak (Malaysia) menjadi masalah yang krusial dari sisi hukum. Barang illegal yang masuk ke wilayah Perbatasan Aruk Kabupaten Sambas, seperti : pakaian bekas, elektronik bekas, rokok produk luar negeri yang tidak dilekati pita cukai Indonesia, minuman keras, dan produk lainnya. Barang tersebut masuk ke wilayah Indonesia melalui Perbatasan Aruk Kabupaten Sambas secara illegal bertujuan untuk menghindari kewajiban pembayaran bea masuk dan izin peredaran dari instansi teknis terkait. Rumusan masalah dalam penelitian ini adalah Mengapa Penegakan Hukum Oleh Penyidik Pegawai Negeri Sipil Bea Dan Cukai Terhadap Tindak Pidana Penyeludupan Minuman Keras Illegal Di Kabupaten Sambas Belum Maksimal. Hasil penelitian ditemukan tindak pidana penyeludupan minuman keras dari Sarawak ke perbatasan Aruk kabupaten Sambas dari berbagai merk terkenal. Jumlah kasus tindak pidana penyeludupan minuman keras dari Sarawak ke wilayah perbatasan aruk kabupaten sambas selama 2018-2022 sebanyak 53 kasus, dimana pada tahun 2018 telah terjadi 10 kasus tindak pidana penyeludupan, pada tahun 2019 telah terjadi 8 kasus, tahun 2020 terjadi 5 kasus, tahun 2021 terjadi 14 kasus tindak pidana penyeludupan, dan pada tahun 2022 terjadi 26 kasus tindak pidana penyeludupan minuman keras dari Sarawak ke wilayah perbatasan Aruk kabupaten Sambas dan terdapat 20 kasus tindak pidana yang naik ke tingkat kejaksaan. Upaya penanggulangan penyeludupan oleh PPNS Bea dan Cukai dengan memberikan penyuluhan hukum kepada warga masyarakat di wilayah perbatasan aruk kabupaten sambas mengenai Undang-undang Nomor 17 Tahun 2006 tentang Perubahan Atas Undang-undang Nomor 10 Tahun 1995 tentang kepabeanan; dan memperketat penjagaan di wilayah di wilayah perbatasan terutama jalan-jalan tidak resmi yang dijadikan akses terjadinya penyeludupan minuman keras illegal. Kata Kunci : Penyeludupan, Penegakan Hukum, Pelaku Penyeludupan, Minuman Keras Illegal, Aparat Penegak Hukum.